Avaliação dos níveis de TAFI (inibidor da fibrinolise ativado pela trombina), do PAI-1 (inibidor do ativador do plasminogênio tipo 1) e frequência de seus polimorfismos na dislipidemia - Izabela Ribeiro Santos (2013)
Cardiovascular diseases are a public health concern with high morbidity and mortality, affected by risk factors such as diabetes mellitus, smoking, physical inactivity, hypertension, obesity and dyslipidemia. Dyslipidemia is defined as alterations in lipid metabolism that change the levels of lipoproteins, constituting a major risk factor for atherosclerosis and its complications. Moreover, it affects the haemostatic system, especially in the fibrinolysis. Several proteins comprising the fibrinolytic system regulates fibrinolysis by acting indirectly on the degradation of the fibrin clot, specially the inhibitor by Thrombin Activatable Fibrinolysis Inhibitor (TAFI) and Plasminogen Activator Inhibitor type 1 (PAI-1). Increased levels of TAFI have been associated with cardiovascular events, as well as increased serum PAI-1, which is already considered as a risk factor for such events. This study evaluated the association of acquired risk factors, the polymorphisms Thr325Ile, Ala147Thr and +1542C/G in the TAFI gene and 4G/5G in the PAI-1 gene and its plasma levels with dyslipidemia through the investigation of 109 dyslipidemic and 105 normolipemic individuals. We conducted analyses of biochemical and lipidic profile, as well as hemostatic parameters (TAFI and PAI-1 by ELISA) and molecular analysis using Polymerase Chain Reaction (PCR) to verify the genotypic and allelic frequencies for the polymorphisms studied. It was observed that hypertension, increased body mass index and menopause are more common in dyslipidemic individuals and they have higher TAFI levels. The alleles 325Ile, Ala147 and C showed association with lower TAFI levels. Ala147Thr and Thr325Ile polymorphisms are independently associated with dyslipidemia in males. The 4G/5G polymorphism and PAI-1 levels were not related with the disease. The results suggest that only TAFI may be independently associated with dyslipidemia.